Evidence of Validity of a Modern Homonegativity Measure against Gays and Lesbians - Lima,Kaline da Silva (2019)
Abstract The goal of this research was to adapt and obtain validity evidence of the Modern Homonegativity Scale (MHS), which is set by two parallel forms with 12 items, one of them referring to gays (MHS-G) and the other referring to lesbians (MHS-L). In the first study 418 heterosexuals between 18 and 58 years old (M = 24,9; SD = 7,23), mostly women (66,3%) living at João Pessoa-PB (50,5%) answered. Both scales have shown as unidimensional and containing a high degree of internal consistency. The second study had the participation of 273 heterosexuals between 18 and 55 years old (M = 23,7; SD = 6,33), mostly women (69%). The confirmatory factor analysis showed satisfactory adjustment indexes for the proposed model and the Item Response Theory (IRT) demonstrated a good degree of discrimination and variation of the difficulty parameters. Therefore, we may conclude MHS is psychometrically valid, easily applicable and can be used in research contexts.